Relationship between Collaboration in Work Support and Knowledge and Skills in Providing Support for Individuals with Disabilities - Maebara, Kazuaki; Yaeda, Jun (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Background: There has been growing hope for initiatives supporting the transition of persons with disabilities from employment-related welfare services to employees in companies. This is against the backdrop of a significant increase in employment among persons with disabilities in Japan. Objective: To improve the quality of this transition, this study examined the relationship between the collaboration of the Work Support Centers for Continuous Employment Type B (WSC-B) with vocational rehabilitation organizations (VROs) and knowledge and skills related to employment support. Methods: A survey including all 122 WSC-B in L-Prefecture was conducted by postal mail. The respondents were asked to rate items on the following six levels concerning collaboration with VROs and understanding of VROs. We used the Japanese version of the Self-Assessment for Students or Counselors (SASC-J) to assess knowledge and skills related to work support. Results: The t-test conducted on knowledge and skills status between WSC-B with a high degree of cooperation with VROs and those with low degrees confirmed significant differences among the various subsystems in VROs. Conclusion: Based on our results, we suggest that maximizing the use of collaboration in work support will enhance the support provided by WSC-B and promote transition support for people with disabilities.